Ijtihād Maqāṣidī and Legal Adaptation: A Comparative Analysis of Contemporary Islamic Jurisprudence in Responding to Emerging Issues - Athambawa, Mahroof (Mazahibuna: Jurnal Perbandingan Mazhab, 2025)
This study aimed to examine the significance of ijtihād Maqāṣidī in contemporary Islamic jurisprudence, focusing on its role in addressing legal and ethical dilemmas. The study explored how Islamic law remains adaptive and relevant in modern contexts by analyzing different scholarly perspectives on Maqāṣid al-Sharīʿah. A qualitative method was adopted, utilizing doctrinal analysis and comparative methodology. Primary and secondary Islamic legal sources, including classical and contemporary juristic opinions, were analyzed to evaluate different schools of thought regarding ijtihād Maqāṣid. Additionally, case studies such as the COVID-19 pandemic and the moon sighting debate were examined to show practical applications of Maqāṣid in Islamic legal reasoning. The result showed three primary methods among contemporary scholars, namely (1) scholars who consider Maqāṣid as an independent legal proof, (2) those who limit Maqāṣid only to explicitly supported textual evidence, and (3) the moderate scholars who integrate textual sources with Maqāṣid to develop balanced legal rulings. The result reflected the strengths and weaknesses of each method, showing how Maqāṣid-based reasoning improves the adaptability of Islamic jurisprudence. This study provided a comprehensive examination of Maqāṣid’s role in contemporary Islamic legal thought, offering a distinct understanding of ijtihād Maqāṣidī beyond traditional jurisprudential analyses. By integrating historical and modern perspectives, the results contributed to ongoing debates on the evolution of Islamic legal methodologies. Furthermore, there was a need for incorporating ijtihād Maqāṣid in modern legal discourse to ensure that Islamic law remained relevant and effective in addressing new societal challenges. This study also advocated for a structured application of Maqāṣid in judicial and legislative frameworks, promoting further investigation into its potential in legal reform and policy-making in Islamic jurisdictions.